Factores que inciden en el otorgamiento de créditos en las entidades bancarias. - Murillo Guevara, Madelyn Gisella (My University, 2019)
This research details the variables that the financial sector, especially banking, analyze in order to carry out the activities corresponding to the nature of these companies, so it has been established that the objective of this study is to determine the factors that mostly affect financial institutions so that they can grant a bank loan, it is important to emphasize that this research is descriptive with a quantitative approach, the econometric methods that have been used for the correct outcome of this study are the probit and logit models, the fundamental reason for selecting these models to explain the central theme is because it allows the researcher to determine between two options that are dichotomous in nature and are represented by the returned variable, an option will be chosen according to the incidence of the return variables, the tool which was used to perform all procedures The statistical software was Stata, the results of the estimates revealed that the variable that has the highest incidence in the model is white with 52%, however to grant greater veracity to the investigation, this variable was omitted and it was obtained that married and chist, the same ones that indicate if the user is married and has a delinquent account with 27% and 62% respectively, are necessary indicators within this analysis, in turn a comparison was made between the results obtained from both models in order to determine how much the behavior of the variables change.
La presente investigación detalla las variables que el sector financiero en especial la banca analizan para poder realizar las actividades correspondientes a la naturaleza de estas empresas, por lo cual se ha establecido que el objetivo de este estudio se centra en determinar los factores que inciden mayormente en las entidades financieras para que puedan otorgar un crédito bancario, es importante destacar que esta investigación es de tipo descriptiva con enfoque cuantitativo, los métodos econométricos que se han empleado para el correcto desenlace de este estudio son los modelos probit y logit, el motivo fundamental de seleccionar estos modelos para explicar la temática central es porque permite al investigador poder determinar entre dos opciones que son de naturaleza dicótoma y se encuentran representada por la variable regresada, se va a elegir una opción de acuerdo a la incidencia de las variables regresoras, la herramienta que se empleó para realizar todos los procedimientos fue el software estadístico Stata, los resultados de las estimaciones dieron a conocer que la variable que mayor incidencia tiene en el modelo es white con 52%, sin embargo para otorgarle mayor veracidad a la investigación, se omitió esta variable y se obtuvo que married y chist, las mismas que indican si el usuario está casado y tiene una cuenta morosa con 27% y 62% respectivamente, son indicadores necesario dentro de este análisis, a su vez se realizó una comparación entre los resultados obtenidos de ambos modelo para poder determinar que tanto cambian el comportamiento de las variables.
Keywords: SECTOR FINANCIERO; CRÉDITOS; PROBIT; LOGIT; WHITE